The real-object advantage in agnosia: Evidence for a role of surface and depth information in object recognition. - Chainay, H; Humphreys, G (2001)
We examine the factors that lead to the identification advantage for real objects over line drawings in agnosia. In a single case study we show that identification is improved when shading cues can be used to guide the segmentation of objects into their parts. In addition we demonstrate that depth information, conveyed both by binocular disparity cues and by head movements, also facilitates object segmentation. The data indicate that information about depth and surface shading can contribute to object recognition in cases where edge-based object coding is impaired.